Censura periodística, análisis de causas, consecuencias y posibles soluciones - Fernández Orellana, Jordan Steven (2023)
The objective of this case study is to determine the causes and consequences of journalist security through virtual surveys. For this investigative work, the deductive method was used, which allowed the necessary information to be obtained through the questions to make comparisons. and investigate, the quantitative methodology was used through virtual surveys that aimed to obtain percentages, to comply with the qualitative method, surveys through social networks were used as a tool, through which highly relevant information was collected, where was able to obtain different opinions from each person, since each person sees the world differently, and it is very important that they express their agreements and disagreements. In conclusion, when conducting the surveys I was able to determine that there are many people who currently do not have knowledge , they are not informed, and they do not use censorship terminology as a topic of conversation, misinformation in the media is not an invention or conception of those who want or desire to dedicate themselves to journalism. In the past, little information flowed, it was easier to recognize the information that you wanted to hide from others.